Post-conflict communities in the Department of Junin: the Canipaco valley and Pariahuanca - Plasencia Soto, Rommel (2018)
Exploraty study that compares two rural post-conflict in the central highlands of the Perú and as the characteristics of these involved not only different forms of the civil war, but also different forms of leadership and community reconstruction. What is wanted to show finally is the dynamic current of these regions in a context of modernization, growth economic and interconnection increased.